Pengaruh Perendaman Larutan Teh Hijau terhadap Perkembangan Embrio Ikan Patin - Eka Wahyu Putr M Ritonga; Amanda Nurul Aisyah Naibaho; Febri Rahmadani Hasibuan (EduInovasi: Journal of Basic Educational Studies, 2023)
Catfish (Pangasius pangasius) is a freshwater fish species that has the potential to be cultivated because it has good reproductive performance, one of which is high fecundity. However, catfish eggs are sticky (adhesive) which causes the eggs to stick together so they cannot be fertilized optimally. Green tea (Camellia sinensis) contains tannins which can reduce the stickiness of eggs. The long soaking process will affect the development of catfish egg embryos because it is suspected that green tea which has a certain threshold can turn into poison because the accumulated dose and time can become poison due to the chemical reactions it causes. Therefore, it is necessary to conduct research to examine the effect of soaking time in green tea solution on reducing the stickiness of eggs. This study aims to determine the effect of soaking time in green tea solution (Camellia sinensis) on the development of catfish embryos and the best time. The observed data is the process of embryology. The results showed that maximum egg development was obtained in Treatment A, namely development up to the organogenesis phase. The conclusion that can be drawn is that the soaking time of green tea solution on catfish eggs has a significant effect on embryo development. Keywords: The catfish (Pangasius pangasius), The green (Camellia sinensis), Embryonic development